An automatic method for generating multiple alignment alternatives for a railway bypass. (June 2023) - Vázquez-Méndez, Miguel E.; Casal, Gerardo; Castro, Alberte; Santamarina, Duarte
Abstract: This paper deals with the problem of designing a bypass on a railway line. Based on a geometrical model capable of determining automatically the need of major structures (bridges, tunnels, overpasses and underpasses), the optimal design of a railway bypass is formulated in the framework of Mixed Integer Non Linear Programming (MINLP), and it is solved with a numerical algorithm which provides different layout alternatives that are optimal solutions (local minima) from the economic point of view. The proposed method is tested on a case study with the aim of showing its practical usefulness as a support tool for engineers in order to accomplish the complex and time-consuming task to generate a set of initial alternatives for the design of a railway bypass. Highlights: A mathematical model for designing multiple railway bypasses is proposed. Main structures (tunnels, bridges, overpasses, and underpasses) are considered. A hand-made initial alignment is not necessary. Multiple suboptimal layouts (local minima) are provided. The model is successfully used in a real case study.